Inter-Art Dynamics of Kalapremi’s Artworks: A Critique of Contemporary Nepali Arts - Hamal, Koshal (The Outlook: Journal of English Studies, 2024)
The 'inter-art' refers to an artwork that is composed of more than one art form of the visual arts, such as sculpture, painting, video art, photography, ceramics, installation, performance, etc., showing the relationship between them. This study reveals the idea of inter-art relationships in the works of Gopal Kalapremi Shrestha, widely known as ‘Kalapremi’. The main objective of this paper is to explore the inter-art dynamics of Kalapremi’s artworks. The paper also aims to identify the key art genres in the creations of Kalapremi and to discuss the underlying meaning of his style. The paper reveals the importance of having multiple skills and techniques for an artist in today's contemporary art contexts. The effect of the inter-art relationship shows the dynamism, progressiveness, limitlessness, and unconventionality of an individual art practice. It mainly focuses on the inter-art relationship as a major tool to analyze creativity.